Optimization of spot welding on vitroperm 500F TL1 (VP 500F) via Taguchi Method - Nur Elora Sofea, Zuraiman; Mas Ayu, Hassan; Juliawati, Alias; Rosdi, Daud (Springer Science and Business Media Deutschland GmbH, 2025)
Magnetic core is produced using strip material Vitroperm 500F TL1 (VP 500F) with thickness ranging 18–21 µm is run through Vitromat winding machine. In this study, welding parameter is investigated by one of a Design of Experiment (DoE) tool using Taguchi method. Taguchi Method of orthogonal L8 design is used to optimize the welding parameter in this experiment. The charging voltage capacitor, start pulse-width, inner pulse width and end pulse width are set up as variable with bounce time (µS) and electrode pressure as fixed parameter. The morphologies of weld zone are evaluated using 3D Laser Microscope to determine the diameter of welding hole, spatters and cracks at start, inner and end position of welding. The result showed by using 12.35 V of charging voltage capacitor and shorter pulse width for start position gives a better result in terms size of welding cracks and diameter hole.